Effect of Independence, Professional Expertise, Work Experience and Performance of Supervisors on the Performance of Savings and Loans Cooperatives in the Province of Bangka Belitung Islands - Duwi Agustina; Wenni Anggita (Fakultas Ekonomi, Universitas Bangka Belitung, 2017)
The purpose of this research is to know and analyze: (1) the influence of independence on the performance of Savings and Loans Cooperative, (2) the influence of professional expertise on the performance of Cooperative Savings and Loans, (3) the influence of work experience on the performance of Cooperative Savings and Loans, and how (4) as well as how the influence of supervisor's performance on the performance of Cooperative Savings and Loans. Research respondents amounted to 171 supervisory cooperatives of Savings and Loans in Bangka Belitung Islands Province spread over 7 districts, such as Bangka, Central Bangka, West Bangka, South Bangka, Pangkalpinang, Belitung and Belitung Timur. The collected data is processed using the quantitative method using Statistical Product and Service Solutions. The results showed that the independent variable, professional expertise, and performance of supervisors did not affect the performance of savings and loan cooperatives, while the working experience variables influence the performance of savings and loan cooperatives in the province of Bangka Belitung Islands.